برنامج البيئة العربية لتنمية مهارة الكلام : (دراسة وصفية تحليلية فى معهد نور الرشاد العزيزية) - Miswarul Abdi Aziz; Muhammad Iqbal (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2022)
Abstrac The objectives of this research: To know the application of the Arabic environment program at the Nour Al-Rashad Al-Aziziyah Institute and to know the ability of the students at the Noor Al-Rashad Al-Aziziyah Institute to speak skill after the application of the Arab environment program, and to know the problems faced by the students of the Noor Al-Rashad Al-Aziziyah Institute in speaking Arabic. The research method that the researcher depends on in this research is the descriptive analytical method. The method used by the researcher in collecting data in this research is direct observation, personal interview, questionnaire and documents. And the sample of the research that the researcher took in this research is the students in the high stage at Noor Al-Rashad Institute Al-Aziziyah, and their number is 35 students. As for the results of the research, they are: The application of the Arab Environment Program at the Nour Al-Rashad Al-Aziziya Institute is not complete, and the students’ ability at the Nour Al-Rashad Al-Aziziya Institute to speak skill after the implementation of the Arab Environment Program is good, and the evidence for it was in fact the students were able to deliver the sermon in Arabic and speak it in their daily lives and the students At Nour Al-Rashad Al-Aziziyah Institute, they face problems in speaking the Arabic language. The problems faced by students are the lack of memorizing vocabulary and the lack of understanding the correct Arabic method.